Informal mentoring in prison. Guide for volunteer mentors - Toma, Cristina Magdalena (Technium Social Sciences Journal, 2022)
The idea of mentoring is used in different areas of life – they vary from students’ support to help for drug-addicted people. Today mentors can and should provide expertise to essentially less experienced individuals to help them advance their careers, enhance their education, and build their networks. While mentoring is an important aspect to leadership training, it doesn't hold to a typical training environment or process. It is tradition has existed even longer than traditional training. Mentoring is a unique and valuable volunteer service in prisons. It can often be the foundation for fundamental, positive change. Mentoring is provided so that each prisoner or ex–prisoner will have a positive influence in life and have a positive contact to assist the prisoner upon release. Mentoring is intended to enhance personal growth through the sharing of experiences and wisdom and to offer a framework for teaching and modeling values and life skills (Sapouna et al., 2011). Mentoring it is mentor’s and mentee’s interaction with a common objective.